Microwave Heating as an Alternative Quarantine Method for Disinfestation of Stored Food Grains - Ipsita Das; Girish Kumar; Narendra G. Shah (International Journal of Food Science)
Insects and pests constitute a major threat to food supplies all over the world. Some estimates put the loss of food grains because of infestation to about 40% of the world production. Contemporary disinfestation methods are chemical fumigation, ionizing radiation, controlled atmosphere, conventional hot air treatment, and dielectric heating, that is, radio frequency and microwave energy, and so forth. Though chemical fumigation is being used extensively in stored food grains, regulatory issues, insect resistance, and environmental concerns demand technically effective and environmentally sound quarantine methods. Recent studies have indicated that microwave treatment is a potential means of replacing other techniques because of selective heating, pollution free environment, equivalent or better quality retention, energy minimization, and so forth. The current paper reviews the recent advances in Microwave (MW) disinfestation of stored food products and its principle and experimental results from previous studies in order to establish the usefulness of this technology.